2014
DOI: 10.1021/ie403505u
|View full text |Cite
|
Sign up to set email alerts
|

Permeability, Solubility, Diffusivity, and PALS Data of Cross-linkable 6FDA-based Copolyimides

Abstract: The intrinsic gas transport properties of thermally treated cross-linkable 6FDA-based copolyimide membranes have been studied. Grafting various sizes of cyclodextrin (CD) to the copolyimide matrix and then thermally decomposing CD at elevated temperatures are an effective method to micromanipulate microvoids and free volume as well as gas sorption and permeation. The pressure-dependent solubility and permeability coefficients were found to follow the dual-mode sorption model and partial immobilization model, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…[13] Meanwhile, lower sorption isotherm of CH 4 than CO 2 indicated that weaker polymer interactions and lower condensability are found between the CH 4 gas molecule and the membrane. [43] From Figure 3, membranes M1 and M2 showed higher CO 2 sorption compared to M0 demonstrated that the membrane capacity for CO 2 sorption increased after incorporating MIL-125 (Ti) and NH 2 -MIL-125 (Ti) fillers into 6FDAdurene polymer. This results also show that extra gas sorption side and good affinity between fillers and CO 2 gas are found in the membranes.…”
Section: Co 2 Plasticization Behaviormentioning
confidence: 90%
“…[13] Meanwhile, lower sorption isotherm of CH 4 than CO 2 indicated that weaker polymer interactions and lower condensability are found between the CH 4 gas molecule and the membrane. [43] From Figure 3, membranes M1 and M2 showed higher CO 2 sorption compared to M0 demonstrated that the membrane capacity for CO 2 sorption increased after incorporating MIL-125 (Ti) and NH 2 -MIL-125 (Ti) fillers into 6FDAdurene polymer. This results also show that extra gas sorption side and good affinity between fillers and CO 2 gas are found in the membranes.…”
Section: Co 2 Plasticization Behaviormentioning
confidence: 90%
“…A similar reduction of permeation flux resulting from compression has been reported for N 2 and CH 4 in rubbery polymers such as PDMS and poly(octylmethylsiloxane) (POMS). 45,46 Besides, as seen in Fig. S6 from the ESI †, both CO 2 and CH 4 permeances follow an exponential tendency as a function of feed pressure as described by Stern et al 47 (Equation S1), with beta (the constant characteristic of the penetrant-membrane system at the testing temperature, 35 °C in this case) values positive for CO 2 (0.11 bar -1 ) and negative for CH 4 (-0.18 bar -1 ).…”
Section: Gas Separation Performancementioning
confidence: 99%
“…A fast-fast coincident PALS spectrometer in our laboratory with a system channel width of 50.53 ps per channel was employed. A detailed description of the PALS experimental process and theory can be found elsewhere [39][40][41][42]. The source was sandwiched between two stacks of membrane samples of around 0.5 mm thick which were previously cut into the square shape with a dimension of 1 Â 1 cm 2 .…”
Section: Characterizationsmentioning
confidence: 99%